The internationalization process of Chinese multinational enterprises: influencing factors and paths under the belt and road initiative - Chen Peng (2022)
An important change that economic globalization has brought to the world is the rise of Emerging Multinational Enterprises represented by China. Due to economic globalization, Chinese multinational enterprises (CMNEs) like China Road and Bridge Corporation (CRBC) have played an increasingly important role and have become a major driving force for globalization. Considering the status of latecomers, CMNEs generally fall short of strong international "resources" or "capabilities" to establish their advantages in international competition, which is strongly promoted by the Chinese government through a series of policies in the "Belt and Road" initiative. However, the late start disadvantage, the "liability of latecomer" and the "liability of emergingness" have caused resistance to their internationalization. Through qualitative research and analysis of CRBC cases in three continents, this thesis reveals four paths of CMNEs' internationalization: progressive, radical, leaping, and tentative internationalization. It furthers identifies a three-step model they follow: "Stepping Out", "Planting In", and "Going Out". The centrality, structural autonomy, direct connections, trust, fine-grained information transfer, and joint problem-solving arrangements of CMNEs in the host country’s market network have been found to be the most important factors affecting their internationalization. To overcome their late start, the liability of latecomer, and the liability of emergingness in the context of the "Belt and Road" Initiative, CMNEs rely on policy stimulus, resource endowment and network location between China and the host country. They gain insights into the needs of target customers and integrate resources to provide cost-effective solutions that are highly compatible with customer needs and mitigate resource disadvantages.